Glass in architecture from the pre- to the post-industrial era : production, use and conservation - Wolf, Sophie; Wolf, Sophie; Hindelang, Laura; Hindelang, Laura; Giese, Francine; Giese, Francine; Krauter, Anne; Krauter, Anne (Arts du verre, 2024)
Glass is one of the most fascinating and versatile building materials in architectural history. The new insights into glass in architecture brought together here are the result of research at the intersection of glass production, construction technology and building culture, from Roman times to the present day. Coming from different disciplines, the contributions bridge the divide between natural sciences, humanities, and practical conservation